Generation of cargo trips in urban areas (Research, Society and Development, 2023)
The generation of freight trips in urban areas triggers problems such as traffic congestion, environmental fuel, the consumption of non-renewable energy sources, in addition to the emission of atmospheric pollutants known as AP and greenhouse gases. Faced with the exposed reality, the need for change through government incentives is notorious. With this, the present work aims to analyze how new forms of last mile delivery operation can be adopted in the context of a developing country. As specific objectives, I propose to identify alternatives to TUC activities in Brazil; Investigate how alternatives can be adopted in developing countries in favor of sustainability and identify the main challenges and impacts of urban cargo transport practices between cities that face infrastructure problems. This is a bibliographic review, whose collection was found in the electronic databases indexed: Scientific Electronic Library Online (SCIELO) and Google Scholar. Among the inclusion criteria, articles that met the objectives of this research were used, discarding those that did not meet the relevant theme, as well as the publication period established at 10 years. The results here demonstrated that new forms of use adopted in the last mile in relation to the reality of a developing country like Brazil. Among the forms of use, the use of electric bicycles and tricycles for cargo, the use of drones, the use of autonomous vehicles, crowdsourcing, delivery directly in the trunk of the car and delivery at collection points were pointed out. Finally, it was concluded that the last mile measures have the potential to be customers in Brazil, as long as public investments start to pay attention to road maintenance, spaces for bicycles, in addition to investment in safety.